How does it change?

Algebra Level 2

Consider f ( x ) = s i n ( x ) f\left( x \right) =sin(x) and other function h ( x ) = g ( x ) . f ( x ) h\left( x \right) =g\left( x \right) .f\left( x \right)

What should be g ( x ) g\left( x \right) . If the following holds true

  • h ( x ) = f ( x ) h\left( x \right) =f(x)\quad when x 0 x\ge 0

  • h ( x ) = 0 h\left( x \right) =0\quad when x<0

Note

  • x R x\in R\quad

  • sgn is sign(signum) function

  • abs is absolute value or |sinx|

g ( x ) = s g n ( tan x ) + 1 2 g\left( x \right) =\frac { sgn(\tan { x) } +1 }{ 2 } g ( x ) = s g n ( cos x ) + 1 2 g\left( x \right) =\frac { sgn(\cos { x) } +1 }{ 2 } g ( x ) = a b s ( s i n x ) s i n x g\left( x \right) =\frac {abs(sinx) }{ sinx } g ( x ) = s g n ( sin x ) + 1 2 g\left( x \right) =\frac { sgn(\sin { x) } +1 }{ 2 }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kandarp Singh
Dec 9, 2017

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...